1969
DOI: 10.1080/0028825x.1969.10428593
|View full text |Cite
|
Sign up to set email alerts
|

Growth rings in rimu from south Westland terrace forest

Abstract: A study of growth rings in relatively fast-grown rimu trees from terrace forest in south Westland revealed a number with conspicuously dark latewood bands. These have been called marker rings. The regular occurrence of these marker rings in the same sequence in a number of trees indicates that growth rings are formed contemporaneously in all relatively fast growing trees. A good correlation between the occurrence of marker rings and cool autumn temperatures in the years in which they were formed is very strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…In this setting, the onset of the cool, dark winter would be the most likely trigger of cambial dormancy and growth ring formation, and individual ring increments in the woods therefore probably represent an annual growth period (Francis, 1986). Furthermore, in the closest modern analogues to the vegetation of the Triton Point Formation, the cool temperate podocarp forest of South Island, New Zealand, conifers usually only make one growth ring per annum (Franklin, 1969). Assuming that growth rings were formed annually, the fossil leaf trace data indicate that Araucariopitys and Podocarpoxylon sp.…”
Section: B2 Data and Interpretationmentioning
confidence: 97%
“…In this setting, the onset of the cool, dark winter would be the most likely trigger of cambial dormancy and growth ring formation, and individual ring increments in the woods therefore probably represent an annual growth period (Francis, 1986). Furthermore, in the closest modern analogues to the vegetation of the Triton Point Formation, the cool temperate podocarp forest of South Island, New Zealand, conifers usually only make one growth ring per annum (Franklin, 1969). Assuming that growth rings were formed annually, the fossil leaf trace data indicate that Araucariopitys and Podocarpoxylon sp.…”
Section: B2 Data and Interpretationmentioning
confidence: 97%
“…f. was annual and concluded that New Zealand subalpine woody plants show a well marked periodicity of growth. In a detailed study Franklin (1969) demonstrated that growth rings in Westland rimu are normally formed annually although false rings are occasionally formed in fast growing trees. Wells (1972) showed that over 6 years, annual growth rings were produced in each of 20 marked PodocarplIs hallii trunks.…”
Section: Introductionmentioning
confidence: 99%
“…None of the trees was strongly fluted, an important consideration in assessing ring spacing (Franklin 1969). Using a 5 mm diameter increment borer, five continuous cores c. 25 cm long were extracted from each tree c. 5 cm apart in a ,1937,1972,1993 Ridge crest above bluff, seaward end of colony 1765,1831,1894,1965Ridge crest 1874, 1908, 1940,1980 vertical line at c. 1.5 m height, and sloped upwards c. 5° to prevent retention of rainwater after sampling.…”
Section: Tree Sampling and Measurement Of Ring Spacingmentioning
confidence: 99%